Segment-by-segment assessment of left ventricular myocardial affection in Anderson-Fabry disease by non-enhanced T1-mapping. (August 2017) - Walter, Thula C; Knobloch, Gesine; Canaan-Kuehl, Sima; Greiser, Andreas; Sandek, Anja; Blaschke, Daniela; Denecke, Timm; Hamm, Bernd; Makowski, Marcus R
Background: Anderson-Fabry disease (AFD) is an X-linked lysosomal enzyme disorder associated with an intracellular accumulation of sphingolipids, which shorten myocardial T1 relaxation times. Myocardial affection, however, varies between different segments. Purpose: To evaluate the specific segmental distribution and degree of segmental affection in AFD patients. Material and Methods: Twenty-five patients with AFD, 14 patients with hypertrophic cardiomyopathy (HCM), and 21 controls were included. A Modified Look-Locker Inversion Recovery sequence (MOLLI) was used for non-enhanced T1 mapping at 1.5 T in addition to standard cardiac imaging in 10–12 short axis views. T1 values were evaluated with a mixed model ANOVA and regression analysis to determine the best diagnostic cutoff values for T1 for each myocardial segment. Results: Regression analysis showed the best diagnostic cutoff compared to controls in cardiac segments 1–4, 8–9, and 14. Mean differences between T1 for AFD versus HCM were greatest in segment 3, 4, and 9 (99 ms, 103 ms, 86 ms, respectively). Overall T1 times were 888 ± 70 ms and 903 ± 14 ms (AFD with and without LVH); 1014 ± 17 ms and 1001 ± 22 ms (HCM and controls, P < 0.05). Conclusion: Myocardial segments are affected by a varying degree of T1 shortening in AFD patients. Segment-specific cutoff values allow the most specific detection and quantification of the extent of myocardial affection.